Implementasi Data Mining Untuk Prediksi Peramalan Penjualan Produk Hj Karpet Menggunakan Metode Linear Regression - Athallah, Muhamad Reza; Rozi, Anief Fauzan (Jurnal Sains dan Teknologi (JSIT), 2022)
HJ Karpet is a business engaged in commerce that sells a variety of carpet types and where inventory is crucial. The problem that HJ Karpet has always faced is an abundance of carpet inventory or overstock. Forecasting with the linear regression method is the solution for assisting with stock planning. Forecasting is the process of calculating future values using historical information. This study used linear regression to calculate and design the system, which was then implemented as a system. This study's objective is to forecast sales of HJ Karpet products using historical sales data provided by HJ Karpet for the purpose of generating a sales forecast. This study resulted in the development of a sales forecasting system that will be used to provide stock planning recommendations for the subsequent months. The results of the manual calculation using the linear regression equation predict a value of 52,093 for January 2023 with an error MAPE (mean absolute percentage error) calculation value of 5,667205%, indicating that the results of the regression-based forecasting model have a high degree of accuracy.